Asia-Pacific Countries with Special Needs Development Report 2023 - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2023)
The Asia-Pacific Countries with Special Needs Development Report is a recurrent ESCAP annual publication that discusses issues of interest for Asia-Pacific least developed countries (LDCs), landlocked developing countries (LLDCs) and small island developing States (SIDS), collectively referred to as countries with special needs (CSN). The Asia-Pacific Countries with Special Needs Development Report 2023: Strengthening Regional Cooperation for Seamless and Sustainable Connectivity examines how regional cooperation on seamless and sustainable connectivity can facilitate a long-term transformation towards a net zero carbon emissions future. Recognising ongoing efforts and existing initiatives and considering the large financing gaps in the countries in special situations, the Report underscores the need to seek synergies between transport, energy, and digital connectivity initiatives in the region.